PENINGKATAN HASIL BELAJAR MATERI PECAHAN DENGAN MODEL PEMBELAJARAN PAKEM SISWA SEKOLAH DASAR - Asri Putri Anugraini; Anik Kurniawati (Program Studi Pendidikan Matematika, 2020)
Learning success is created if students want to be serious in learning, active, creative in solving math problems. The focus of the study was the learning process by improving the mathematics learning system on fractions (multiplication of fractions) with the PAKEM approach. By improving the learning system in the classroom, it can lead to success in increasing students' abilities actively, independently, and creatively. So that researchers commit to strive for improvement of the quality of learning. The research used by researchers was Classroom Action Research (PTK). The subjects of this classroom action research were students of grade V SD Mangunrejo 2, totaling 20 students. The results of the research cycle I and cycle II increased from 74,90% to 80,20%.